(untitled) (CIPEEX, 2026)
INTRODUCTION: The study of Oral Potentially Malignant Disorders (OPMD) plays a crucial role in the prevention of oral cancer. Even after the OMS standardization in 2017, inconsistencies in nomenclature persist. This study aims to contribute to the uniformization of diagnostic criteria. OBJECTIVE: To perform a bibliometric analysis of terminology use in the 100 most cited articles on OPMD between 2017 and 2024. METHODS: Following PRISMA guidelines, a comprehensive bibliometric search was conducted in the Web of Science, resulting in articles on OPMD. After applying eligibility criteria, the top 100 most cited articles were analyzed. Network analyses evaluated terminology trends and collaborative networks. RESULTS: Among the top 100 articles, most adopted the term “OPMD,” as endorsed by WHO in 2017; however, 59 articles continued to use non-standardized or hybrid terminology. The most common associated keywords were “OPMD” and “Oral Premalignant Lesion.” A progressive increase in the use of “OPMD” was observed. Among professionals who used the term “OPMD,” the majority (63.7%) were dentists, while 36.3% represented other professions. Most articles with non-standardized keywords had authors from Asia and Europe, whereas institutions in the United Kingdom tended to adopt “OPMD.”CONCLUSIONS: Although the term “OPMD” has gained greater acceptance, the use of non-standardized terminology still persists. This study highlights the need for consistent terminology, advocating for the adoption of “OPMD” to improve research coherence, facilitate interdisciplinary understanding, and support clinical decision-making.